Dança Joaquim com Zabé, Luiz com Iaiá, dança Janjão com Raqué e eu com Sinhá: a espetacularização da festa e o caráter performativo do gênero nos festejos juninos - Barroso, Hayeska Costa (2019)
The June festivities in Brazil constitute a field of practices involving cultural, political, social and economic issues. The way that agents structure and are structured in this scenario involves not only the place they occupy and / or the role they play. In most approaches to traditions, popular cultures, and parties, the way these same agents constitute their subjectivity and how it affects the very configuration of the feast, its modus operandi, has not been the predominant tonic. Issues relating to gender, sexuality, race / ethnicity, and generational aspects, however, cross festive celebrations and their collective rites of consecration. It is necessary, therefore, to make them visible, in order to discover how they are expressed in the field and what the meanings they contain in the web of relations and disputes, both material and symbolic. Thus, the present research aims to investigate the expressions and codes of gender and sexualities in the field of the June party in Fortaleza-Ce. Its specific objectives are: to analyze the interfaces between the performative character of the genre and the cultural performances in the Junino context; to identify the structures and devices of the Junino festive field in its spectacular expression; and, understand how the performance of public power affects and / or affects the way of being of the June celebrations. Methodologically speaking, the Junina gang is considered the privileged moment in which the observation of these aspects is performed, especially the performative character of the genre associated with the continuous process of spectacularization of the party. As strategies for data collection, the following techniques and instruments were used: documentary analysis, semi-structured interview, questionnaire and direct observation. The presence of trans-quadrille individuals, assuming the role of dancers, was the starting point for the initial questioning of the investigation. The premise is that some festivals and manifestations of popular culture, such as the June festival, the carnival, the feast of the ox and the maracatu, are essentially generated from a heteronormative prism; which does not prevent the reissue of traditional symbols under which they themselves were engendered, especially in relation to gender roles and sexuality, constituting a gender habitus that sometimes stresses and subverts certain patterns, and ratifies them. It is around and from it that the festival enshrines its collective ritual involving artistic and aesthetic languages such as dance, music, theater, fashion and crafts. The results also pointed to the evidence that the June party became a powerful space for trans / gay visibility, even though it continues to express aspects of a predominantly heteronormative and binary social structure as a hegemonic gender pattern. As a cultural product that is, such a party is not shielded from contemporary transformations when it comes to openness to the plurality and heterogeneity of gender issues.